2009
DOI: 10.1007/s10311-009-0240-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heavy metal levels in medicinal plant Hemerocallis minor Miller by X-ray fluorescence spectrometry

Abstract: Contamination of edible plants by toxic metals is a threat for human health. We applied for the first time applied the non-destructive X-ray fluorescence spectrometry (XRF) to determine concentrations of heavy metals, i.e., Fe, Ti, Mn, Cr, Cu, Ni, Zn, Sr and Ba in plant Hemerocallis minor Miller and soils. Because this plant is used in folk medicine, the metal content assessment is important for specifying relevance of application to produce drugs. This paper considers the distribution of elements between diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 2 publications
(2 reference statements)
0
17
0
1
Order By: Relevance
“…Additionally, Anderson [30], an FDA researcher, used hand-held XRF analyzer for determining toxic elements in tableware. While Chuparina and Aisueva [31] determined heavy metals in medicinal plants using XRF, as well as Bueno and Romão [32] determined P, Ca, Ti and Fe in counterfeit medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Anderson [30], an FDA researcher, used hand-held XRF analyzer for determining toxic elements in tableware. While Chuparina and Aisueva [31] determined heavy metals in medicinal plants using XRF, as well as Bueno and Romão [32] determined P, Ca, Ti and Fe in counterfeit medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous plant species used as remedies in traditional medicine are grown as spontaneous flora (Chuparina and Aisueva 2011). In Romania, among the most used medicinal plants in folk medicine are chamomile (Matricaria recutita), milfoil (Achillea millefolium), rattle (Hypericum perforatum), brotherwort (Thymus serpyllum), pot marigold (Calendula officinalis), linden (Tilia platyphyllos), and peppermint (Mentha piperita).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of medical science and the deepening of pharmacology study, the relationship between major or trace elements in natural medicines and pharmacological effect become a new research focus, the analysis of elements and elemental speciation has been more common reported [4][5][6][7] . At the same time, heavy metal pollution in natural medicines has been causing widespread concern [8][9][10][11][12] . Measuring and controlling the contents of heavy metals in natural medicines have practical significance to evaluate the potential human health risks and promote better use of natural medicines.…”
Section: Introductionmentioning
confidence: 99%